LAW APPLICABLE FOR THE REPRESENTATIONTO EXERCISE THE CORPORATE RIGHTS OF SHAREHOLDERSIN POLISH COMPANIES - Tapek, Krzysztof (Review of European and Comparative Law, 2017)
Shareholders of Polish companies dispose of various rights – property as well as corporate. Majority of corporate rights can be exercised by a representative. Representation, in this regard includes two categories: proxy and statutory rep-resentation. Regulations concerning representation vary, depending on kind of company in which they are used (limited liability companies, joint – stock com-panies or public companies, whose regulation is influenced by European law). In current study representation to exercise corporate rights of shareholders will be examined on the meta-law level. Provisions of international private law shall be observed to determine that which country’s legal regime shall be applied to interpret the institution of representation in cross-border situations. Additionally, it is necessary to distinguish the scopes of laws applicable for different issues connected with representation. The dissertation is aimed to address all abovementioned questions with the reference to European and Polish law.